PRAMANA DALAM PERSPEKTIF PENALARAN FILSAFATI - Putu Maria Ratih Anggraini; Ayu Veronika Somawati (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
Pramana or the way to observe or know knowledge is a method used to find truth in the Hindu tradition. Pramana is divided into 3 parts commonly referred to as Tri Pramana, namely Pratyaksa Prana or direct observation giving us knowledge about objects according to their respective circumstances. Anumana Pramana seeks the truth based on 5 (five) things, namely 1) Pratijana, namely introducing the object of the problem about the truth of observation, 2) Hetu,namely the reason for deviation, 3) Udaharana, which connects with the general rules about a problem, 4) Upanaya, namely the use of rules The general is in the fact that seen, and 5) Nigama, in the form of correct and definite conclusions from all previous processes. Sources that are related to the problems faced are not valid or valid in their existence so that the sources that have a relationship are included to strengthen their opinions and help in drawing conclusions tobe analyzed in search of the true truth. The third Pramana is Upamana Pramana is a way of observing by comparing the similarities that may occur or are contained in objects observed with objects that already exist or have been known. This comparison is used as a helper and complementary in the analysis process and draws a conclusion from the problem at hand.